Analysis Of The Role Of Alternative Financing In Sustainable Development - Riza Rasyid Al-Aufa Siagian; Isnaini Harahap; Windu Anggara (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the role of crowdfunding, impact investing, zakat, and waqf as alternative financing in supporting sustainable development in Indonesia. The research method used is qualitative descriptive with a case study approach based on secondary data from literature and empirical reports. The results show that crowdfunding mobilizes community funds for environmental projects such as mangrove conservation in Kalimantan, significantly reducing carbon emissions. Impact investing supports strategic sectors like Islamic fintech and affordable housing, creating both social and financial impact. Zakat contributes to improved welfare through skills training and healthcare services, while waqf supports the development of sustainable social infrastructure. However, the management of zakat and waqf faces challenges in transparency and public participation. This study bridges the literature gap with empirical evidence highlighting the effectiveness of alternative financing in sustainable development. The conclusion emphasizes the need for a strategic integration of alternative financing to accelerate the achievement of sustainable development goals in an inclusive manner.